#### Answer

$g'(t) = 6t - \frac{42}{t^8}$

#### Work Step by Step

$g(t) = 3t^2+\frac{6}{t^7} = 3t^2 + 6t^{-7}$
Power rule: $g'(t) = 3(2)t^{(2-1)} + 6(-7)t^{(-7-1)} = 6t - \frac{42}{t^8}$

Published by
Pearson

ISBN 10:
0321947347

ISBN 13:
978-0-32194-734-5

$g'(t) = 6t - \frac{42}{t^8}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.